EDUKASI ECO ENZYME DARI LIMBAH BUAH DAN SAYUR MENJADI SABUN CAIR CUCI TANGAN SEBAGAI UPAYA MENCIPTAKAN EKONOMI MASYARAKAT PRODUKTIF DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS (SDGs) DI KELURAHAN KETINTANG 4 SURABAYA - Umarudin, Umarudin; Syukrianto, Syukrianto; Anidnya, Widya Dara; Wulansari, Silvi Ayu; Aryanti, Evy (Jurnal Abdi Insani, 2024)
The abundance of fruit and vegetable waste in the Ketintang 4 area has a detrimental impact on the surrounding environment. Therefore, it is necessary to implement educational initiatives on utilizing this waste to produce eco-enzyme, which can be used as an active ingredient in liquid hand soap. This activity aims to educate on eco enzymes from fruit and vegetable waste into liquid hand soap as an effort for Clean and Healthy Living Behavior (PHBS) and the "Let's Wash Hands" movement to change community behavior from unhealthy to healthy. The activity method consists of 4 stages: preparation stage, material preparation stage, education and workshop stage, and evaluation stage. This activity showed that the youth organization members were enthusiastic and experienced increased knowledge from the pre-test results, with "yes" answers at 9.33% and "no" answers at 90.67%. The post-test results showed "yes" answers at 82% and "no" answers at 18%. The increase in knowledge in utilizing eco enzymes for their needs and benefits as active ingredients in liquid hand soap has become a valuable product to encourage the surrounding community to wash hands with soap, an effort to prevent the spread of microorganisms. The satisfaction questionnaire results of the community service activity showed a satisfaction rate of with 87.43% very satisfied, 2.57% satisfied, and 0% unsatisfied. This activity strongly supports the SDGs and the KEMENDIKBUD in 2021 in implementing Clean and Healthy Living Behavior (PHBS) for the Ketintang 4 Subdistrict. It can create a productive economy for the community.